2018
DOI: 10.6009/jjrt.2018_jsrt_74.4.326
|View full text |Cite
|
Sign up to set email alerts
|

Effective Techniques to Reduce Radiation Exposure to Medical Staff during Assist of X-ray Computed Tomography Examination

Abstract: SummaryMedical staffs like radiological technologists, doctors, and nurses are at an increased risk of exposure to radiation while assisting the patient in a position or monitor contrast medium injection during computed tomography (CT). However, methods to protect medical staff from radiation exposure and protocols for using radiological protection equipment have not been standardized and differ among hospitals. In this study, the distribution of scattered X-rays in a CT room was measured by placing electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…In this study, radiation safety glasses showed a 51% dose reduction, which was almost the same as previously reported for the protective glasses with 0.07-mm Pb-equivalent thickness (51.3%-60.0%) [7,10,13,28,36,37,38]. Increasing the lead content of radiation safety glasses (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, radiation safety glasses showed a 51% dose reduction, which was almost the same as previously reported for the protective glasses with 0.07-mm Pb-equivalent thickness (51.3%-60.0%) [7,10,13,28,36,37,38]. Increasing the lead content of radiation safety glasses (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Our results proved that intensive care physicians, who are frequently exposed to radiation during CT for "diagnostic" purposes, had an H p (3) of 0.49 mSv/procedure (median) without radiation safety glasses (Table 8). Our data was about the same as the value of H p (3) previously reported for the CT-assistance personnel during "diagnostic" CT scans [28,29]. Furthermore, our data showed a significantly greater H p (3) than the previously reported doses to the lens of the eye for the operator during CT fluoroscopy for "treatment" purposes (Table 1).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Many studies have investigated the occupational radiation dose in interventional radiology (IR), wherein medical staff may be exposed to considerable scattered X-rays. However, few studies have discussed occupational radiation dose in CT examinations [1][2][3][4][5][6]12]. Our literature search did not reveal any report that directly investigated the radiation dose of eye lens as H p (3).…”
Section: Introductionmentioning
confidence: 94%
“…Medical staff members (e.g., physicians, nurses and radiological technologists) occasionally remain in the CT examination room during irradiation to monitor the injection of the contrast media, to restrain the patient, operate medical devices, etc. [1][2][3][4][5][6]. These actions are performed for medical safety/procedures or maintaining image quality.…”
Section: Introductionmentioning
confidence: 99%